The Mother Stands for the Realm That Must Be Exited. Issue 1 (2nd January 2020) - Guralnik, Orna
ABSTRACT: Attempts to narrate the experience of the mother consistently and compulsively collapse into her function, always idealized and overinvested. These massive social projections onto the mother quickly become evidence of her multitude of failures, meanwhile leaving her experience forever emptied of any possible substantive point of interest.